Scandal - Davis, Carl 1936-2023 (British Film Institute, 2020)
"England 1963. Durch die Vermittlung eines angesehenen Londoner Arztes steigt die junge Christine Keeler in gehobene britische Gesellschaftskreise auf und wird nach verschiedenen Affären zum Auslöser eines politischen Skandals, der den Verteidigungsminister zum Rücktritt zwingt. Ein Jahr danach kommt die oppositionelle Partei nach einem erdrutschartigen Wahlsieg an die Macht. Nach den authentischen Ereignissen des als "Profumo-Affäre" bekannt gewordenen Sex- und Politskandals [...] inszeniert." [filmdienst.de]
Original: Großbritannien 1989
special features: feature commentary by producer Stephen Woolley and writer Michael Thomas ; feature commentary by director Michael Caton-Jones ; "The minister, the model and the russian spy: making 'Scandal'" (2010, 25 mins): members of the Scandal cast and crew discuss the film ; "Michael Caton-Jones remembers 'Scandal'" (2019, 27 mins, Blu-ray only): new interview in which the director recalls making the film ; "Stephen Woolley remembers 'Scandal'" (2019, 40 mins, Blu-ray only): the producer on how he got the film made and the talent he worked with ; "Nothing has been proved": official music video performed by Dusty Springfield (1989, 5 mins) ; "Cabaret girl" (1956, 26 mins): documentary on Murray’s Cabaret Club, shot shortly before its owner hired Christine Keeler and Mandy Rice-Davies as dancers ; "The riveter" (1986, 35 mins): short by Michael Caton-Jones, made while he was a student at the National Film and Television School ; trailer ; stills gallery
Keywords: Film